Tradition of Criticizing Antiques on Full Moon Nights: Local Wisdom Heritage of Lingga Regency - Lexminander Lexminander; Mariono Mariono; Syafitriandy Syafitriandy; Bambang Bambang; Zaitun Zaitun (SHS Web of Conferences)
This study aims to understand more deeply the symbolic meaning, religious value and social value of the Tradition of Criticizing Antiques on Full Moon Nights, as an effort to preserve ancestral heritage in the midst of modernization. The tradition of criticizing antiques on full moon nights is a form of local wisdom of the Lingga community, which is rich in historical and spiritual values. This ritual is carried out every full moon, aiming to honor heirlooms that have mystical powers and ancestral heritage. Antiques are taken out and assessed by the community, this tradition is called “criticizing the Full Moon” which is the time when natural energy and the supernatural world reach their peak, this ritual is a means of communicating with the universe and maintaining spiritual balance. The study used a qualitative case study approach, data was collected through in- depth interviews, participatory observation and literature studies. In terms of case studies, this tradition is carried out in Lingga Regency, precisely in the Capital City of Daik Lingga. The results of the study show that the tradition of criticizing antiques on full moon nights contains symbolic meaning and has religious value. This ritual strengthens social relations in the community and emphasizes local cultural identity.